1990
DOI: 10.1017/s0022215100112897
|View full text |Cite
|
Sign up to set email alerts
|

Hearing conservation in acoustic neuroma surgery via the posterior fossa

Abstract: An increasing number of patients with an acoustic neuroma present with useful hearing in the tumour ear. Surgical removal of these tumours via the posterior fossa route may enable preservation of the cochlear nerve and otic capsule without increasing the morbidity to the facial nerve. The results of treating 51 cases of acoustic neuroma via the posterior fossa is presented. Forty four tumours measured less than 20 mm in diameter in the cerebellopontine angle and surgery was undertaken with hearing preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…It has been suggested that hearing itself should be evaluated by a combination of pure-tone audiometric findings and speech discrimination score. 7,16 In our previous communication, we proposed that data on the following ten items should be given for consistent evaluationl4: (1) surgical approach; (2) the total number of cases; (3) the incidence of tumors extending 20 mm or less into the posterior fossa; (4) the number of cases of attempted hearing preservation; (5) the number of cases with hearing preserved; (6) the number of cases with 50/50 hearing preoperatively; (7) the number of cases with a tumor of 20 mm in diameter or smaller and 50/50 hearing postoperatively; (9) the number of cases with a tumor of 20 mm in diameter or smaller preoperatively and the 50/50 hearing postoperatively; and (10) the duration of postoperative follow-up. Unfortunately, only a few studies have given the information in all these categories.…”
Section: Facial Nerve Preservationmentioning
confidence: 99%
“…It has been suggested that hearing itself should be evaluated by a combination of pure-tone audiometric findings and speech discrimination score. 7,16 In our previous communication, we proposed that data on the following ten items should be given for consistent evaluationl4: (1) surgical approach; (2) the total number of cases; (3) the incidence of tumors extending 20 mm or less into the posterior fossa; (4) the number of cases of attempted hearing preservation; (5) the number of cases with hearing preserved; (6) the number of cases with 50/50 hearing preoperatively; (7) the number of cases with a tumor of 20 mm in diameter or smaller and 50/50 hearing postoperatively; (9) the number of cases with a tumor of 20 mm in diameter or smaller preoperatively and the 50/50 hearing postoperatively; and (10) the duration of postoperative follow-up. Unfortunately, only a few studies have given the information in all these categories.…”
Section: Facial Nerve Preservationmentioning
confidence: 99%
“…6,30,32,50,51,56,62,77,78,86,92 Glasscock and others submitted that no patient should be excluded from surgery based on tumor size alone. 7,36,55,97 Several groups have supported this position, declaring that aggressive tumor removal as early as possible provides the greatest chance of hearing preservation.…”
mentioning
confidence: 99%
“…Furthermore, it is exceedingly rare that the cochlear nerve passes through the tumor itself. In recent years much attention has been placed on attempts to preserve hearing in patients with good-to-moderate preoperative function, [2,7,12,16,23,27,34] especially regarding the inverse relationship between the size of acoustic tumors and postoperative hearing outcome. [12,27,40] In our experience, we find that preservation of functional hearing is a realistic goal even in patients with larger tumors (Groups 2 and 3), but predicting the patient's ultimate hearing status on the basis of anatomical preservation of the cochlear nerve and intraoperative BAEP monitoring is much less predictable.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, great advances in neuroimaging, cranial nerve monitoring, and microsurgery have shifted the focus of acoustic neuroma surgery from prolongation of patient life to preservation of cranial nerve function, [37] which has led to extraordinary improvements in patient outcomes, with reports from modern series of up to 90% postoperative normal or near-normal facial nerve function [1,3,19,22,25,33,36] and 40% hearing preservation. [2,7,12,15,16,21,23,27,34] A significant number of patients, however, still develop postoperative cranial nerve dysfunction. Consequently, further efforts to refine operative techniques and improve intraoperative monitoring to preserve maximum cranial nerve function continue to be made.…”
mentioning
confidence: 99%